Internal Qualification and Credentialing of Radiation Oncology Physicists to Perform Patient Special Procedures - Mills, Michael D. (Frontiers in Oncology, 2014)
In the arena of radiation oncology special procedures, medical physicists are often the focus professionals for implementation and administration of advanced and complex technologies. One of the most vexing and challenging aspects of managing complexity concerns the ongoing internal qualification and credentialing of radiation oncology physicists to perform patient special procedures. To demonstrate ongoing qualification, a physicist must a) document initial training and successful completion of competencies to implement and perform this procedure, b) demonstrate familiarity with all aspects of the commissioning and quality assurance process, c) demonstrate continuing education respecting this procedure, d) demonstrate the peer-reviewed completion of a minimum number of patient special procedures during a specified time span, and e) demonstrate satisfactory overall progress toward maintenance of specialty board certification. In many respects, this information complement is similar to that required by an accredited residency program in therapy physics. In this investigation, we report on the design of a management tool to qualify staff radiation oncology physicists to deliver patient procedures.